2016
DOI: 10.1007/s11626-016-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the role of extracellular -5′- nucleotidase in breast cancer stem cells and epithelial-mesenchymal transition

Abstract: Tumor stem cell theory may well explain a variety of malignant behaviors of tumors. Cells undergoing epithelial-mesenchymal transition (EMT) share many characteristics with tumor stem cells. Our previous studies showed that extracellular -5'- nucleotidase (CD73), one of the important surface markers of mesenchymal stem cells, may promote growth and metastasis of breast cancer cells both in vivo and in vitro. In this study, we assessed breast cancer stem cell (BCSC) markers [acetaldehyde dehydrogenase (ALDH) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The coexpression of both CD73, which generates adenosine, and A2BR, which is activated in response to adenosine binding, constitutes an autocrine signaling pathway leading to STAT3dependent expression of NANOG, a pluripotency factor that specifies the BCSC phenotype. These findings may explain previous studies reporting that CD73 activity promoted the BCSC phenotype (60). We previously reported that hypoxia induces HIF-dependent demethylation of N 6 -methyladenosine residues leading to stabilization of NANOG mRNA, thereby stimulating BCSC accumulation (61,62).…”
Section: Discussionsupporting
confidence: 70%
“…The coexpression of both CD73, which generates adenosine, and A2BR, which is activated in response to adenosine binding, constitutes an autocrine signaling pathway leading to STAT3dependent expression of NANOG, a pluripotency factor that specifies the BCSC phenotype. These findings may explain previous studies reporting that CD73 activity promoted the BCSC phenotype (60). We previously reported that hypoxia induces HIF-dependent demethylation of N 6 -methyladenosine residues leading to stabilization of NANOG mRNA, thereby stimulating BCSC accumulation (61,62).…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, increased CD73 levels were detected in cell lines of breast carcinoma undergoing EMT-induced by TGF-β. [52,53] While EMT is a hallmark of a more aggressive phenotype and is also induced by HIF-1, TGF-β is secreted by tumors and has an immunosuppressive role similar to that of CD73. [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the expression and function of CD73 in other types of stem cells, in particular in CICs. In fact, to our knowledge, the functional contribution of CD73 to CICs has been reported only in cell lines from pancreatic neuroendocrine ( Katsuta et al., 2016 ) and mammary tumors ( Yu et al., 2017 ). The role of CD73 in OCIC function is consistent with previous reports on the expression and the biological activity of CD73 in OC.…”
Section: Discussionmentioning
confidence: 96%